2017
DOI: 10.1111/tpj.13623
|View full text |Cite
|
Sign up to set email alerts
|

JMJ27, an Arabidopsis H3K9 histone demethylase, modulates defense against Pseudomonas syringae and flowering time

Abstract: Histone methylation is known to dynamically regulate diverse developmental and physiological processes. Histone methyl marks are written by methyltransferases and erased by demethylases, and result in modification of chromatin structure to repress or activate transcription. However, little is known about how histone methylation may regulate defense mechanisms and flowering time in plants. Here we report characterization of JmjC DOMAIN-CONTAINING PROTEIN 27 (JMJ27), an Arabidopsis JHDM2 (JmjC domain-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 78 publications
(91 reference statements)
1
70
0
Order By: Relevance
“…However, similar roles in the regulation of immunity may occur in related proteins. For instance, some proteins belonging to the Jumonji-C demethylase family contribute to immunity by repressing the expression of negative regulators of defense: Arabidopsis JMJ27 represses WRKY25 and WRKY33 by removing H3K9me1/2, while rice JMJ704 is necessary for the repression of OsWRKY66, NRR, and Os-11N3 via H3K4me2/3 demethylation [83,84]. Among the methyltransferases that have been reported to have a role in immunity are ATX1, SDG25, and SDG8, mutants of which are defective in basal defense, necrotroph resistance, and SAR, respectively [85][86][87][88].…”
Section: Defense and Epigeneticsmentioning
confidence: 99%
“…However, similar roles in the regulation of immunity may occur in related proteins. For instance, some proteins belonging to the Jumonji-C demethylase family contribute to immunity by repressing the expression of negative regulators of defense: Arabidopsis JMJ27 represses WRKY25 and WRKY33 by removing H3K9me1/2, while rice JMJ704 is necessary for the repression of OsWRKY66, NRR, and Os-11N3 via H3K4me2/3 demethylation [83,84]. Among the methyltransferases that have been reported to have a role in immunity are ATX1, SDG25, and SDG8, mutants of which are defective in basal defense, necrotroph resistance, and SAR, respectively [85][86][87][88].…”
Section: Defense and Epigeneticsmentioning
confidence: 99%
“…JMJ27, a jumonji-family demethylases, removes repressive H3K9me2 and H3K9me1 marks and thereby activates transcription. ChIP analysis revealed that the chromatin at the WRKY25 promoter was hyper-methylated in jmj27 mutants indicating that JMJ27 regulates WRKY25 expression at least in part by directly controlling methylation levels of H3K9 histones (Dutta et al, 2017). WRKY53 expression is also regulated by epigenetic changes in histone methylation (Ay et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Histone modifications potentially provides a reversible and dynamic way to regulate many biological processes including plant immunity (Ramirez‐Prado et al , ). In Arabidopsis, histone deacetylase HDA6 (Wang et al , ), HDA19 (Zhou et al , ; Choi et al , ), methyltransferases ATX1 (Alvarez‐Venegas et al , ), ATXR7 (Xia et al , ), SDG8 (Berr et al , ) and SDG25 (Lee et al , ), demethylases FLD (Singh et al , ) and JMJ27 (Dutta et al , ), and H2B monoubiquitinase HUB1 (Dhawan et al , ; Zou et al , ), have been previously shown to affect plant resistance. In this study, we have discovered that JMJ14 is a positive regulator of plant immunity.…”
Section: Discussionmentioning
confidence: 99%